2013
DOI: 10.1001/jamapediatrics.2013.1429
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Deprived Young Drivers and the Risk for Crash

Abstract: Less sleep per night significantly increased the risk for crash for young drivers. Less sleep on weekend nights increased the risk for run-off-road crashes and crashes occurring in the late-night hours. This provides rationale for governments and health care providers to address sleep-related crashes among young drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 50 publications
1
60
0
Order By: Relevance
“…Carter et al [24], using a measure of SD similar to that used in our study, found that self-perceived SD was directly related to accident occurrence in males, both in the general population and in professional drivers. Our results are also consistent with those of other studies on car drivers that demonstrated an association between the amount of hours of sleep per night and MVA [47] or NMA rates [48]. A recent population-based case-control study reported that drivers with 6 hours or less of nocturnal sleep during the previous 3 months were at significantly increased risk of MVAs (> 69%) when compared to those who had slept for more than 6 hours [49].…”
Section: Discussionsupporting
confidence: 93%
“…Carter et al [24], using a measure of SD similar to that used in our study, found that self-perceived SD was directly related to accident occurrence in males, both in the general population and in professional drivers. Our results are also consistent with those of other studies on car drivers that demonstrated an association between the amount of hours of sleep per night and MVA [47] or NMA rates [48]. A recent population-based case-control study reported that drivers with 6 hours or less of nocturnal sleep during the previous 3 months were at significantly increased risk of MVAs (> 69%) when compared to those who had slept for more than 6 hours [49].…”
Section: Discussionsupporting
confidence: 93%
“…4 However, research suggests that sleep quantity and quality may both matter. 2, 3 For example, poor sleep quality 23 and shorter sleep duration 24, 25 have been independently associated with motor vehicle accidents and unintentional injuries in adolescents. The Healthy People 2020 target to increase the proportion of high school students who get sufficient sleep is measured by the proportion of adolescents who self-report getting at least 8 hours of sleep on an average school night in the YRBS.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic sleep loss in adolescents has also been linked to poor judgment, lack of motivation, and inattention (Gradisar, Terrill, Johnston, & Douglas, 2008; Owens, 2014; Wolfson & Carskadon, 1998), and consequently with an increase in risk-taking behaviors, such as drinking and driving, smoking, and delinquency (Catrett & Gaultney, 2009; O’Brien & Mindell, 2005). Driving while drowsy is a frequent complaint among older adolescents, and daytime sleepiness in this demographic has been associated with an increased rate of motor vehicle accidents (Martiniuk et al, 2013; Owens, 2014; Pizza et al, 2010). …”
Section: Introductionmentioning
confidence: 99%